Connexin46 in the nucleus of cancer cells: a possible role as transcription modulator - Ainoa Fernández-Olivares; Viviana P Orellana; Jesús Llanquinao; Gonzalo Nuñez; Pablo Pérez-Moreno; Sebastián Contreras-Riquelme; Alberto JM Martin; Fabio Mammano; Ivan E Alfaro; Juan F Calderón; Jimmy Stehberg; Mauricio A Sáez; et al. (Cell Communication and Signaling)
Abstract Background Oncogenes drive cancer progression, but few are active exclusively in tumor cells. Connexins (Cxs), traditionally recognized as ion channel proteins, can localize to the nucleus and regulate gene expression, playing key roles in both physiological and pathological processes. Cx46, once thought to be restricted to the eye lens, has been implicated in tumor growth, though its underlying mechanisms remain unclear. This study investigates the nuclear presence of Cx46 in cancer cells and its potential role as a transcriptional modulator. Methods We employed ChIP-Seq, confocal immunofluorescence, and nuclear protein purification to assess Cx46 localization and DNA interactions. Functional assays were conducted to evaluate its effects on invasion, division, spheroid formation, and mesenchymal marker expression. Single-point mutations and molecular dynamics simulations were used to explore potential Cx46-DNA interactions. Results Cx46 mRNA upregulation was found in a variety of tumors compared to adjacent healthy tissue. In HeLa cells, which do not express Cx46, its transfection promoted proliferation, invasion and self-renewal capacity, cancer stem cell traits and mesenchymal features. Consistently, in Sk-Mel-2, which naturally express Cx46, reduced Cx46 expression led to a decrease in the similar parameters. In HeLa cells, nuclear Cx46 was detected in two forms, full length 46 kDa and a 30 kDa fragment (GJA3-30 k), ChIP-Seq experiments revealed that Cx46 binds to the DNA at intergenic and promoter regions, leading to the activation of oncogenic pathways. Molecular dynamics simulations suggest that GJA3-30 k dimerizes in a RAD50-like structure, forming stable DNA complexes. Cx46 and in some cases GJA3-30 k were detected in the nuclei of multiple cancer cell lines, including prostate, breast and skin cancers. Conclusions Our findings reveal a novel nuclear role for Cx46 in cancer, demonstrating its function as a transcriptional regulator and its potential as a therapeutic target.